Calibration and validation of an activated sludge model for membrane bioreactor wastewater treatment plants. Issue 15 (2nd July 2020) - Tenore, Alberto; Vieira, João; Frunzo, Luigi; Luongo, Vincenzo; Fabbricino, Massimiliano
ABSTRACT: A mathematical model to simulate the biological processes occurring in a membrane bioreactor (MBR) is presented. The model accounts for different MBR technical features by introducing specific permeability parameters for the applied membrane system. The model considers for the heterotrophic storage process and the formation of soluble microbial products. The introduction of an inhibition coefficient influencing the anoxic kinetics enables the model to simulate the particular operating conditions of the plant, such as a high or low dissolved oxygen concentration in the denitrification tank. The model was applied at the MBR wastewater treatment plant of Vila Nova do Ceira (Portugal) which uses a classic pre-denitrification cycle. Data for calibration and validation were sampled at the same wastewater treatment plant. Calibration was achieved by varying the kinetic parameters of the model to match the simulation results to the experimental data. The values of the kinetic parameters were similar to those found in the literature. The validation was performed by two different methodologies to analyse the model response to diverse operating conditions, and to evaluate the resilience of the MBR. Calibration and validation results were evaluated with mean average error, root mean square error and fractional mean bias as performance indexes. In most cases, these indexes confirmed the high accuracy of the model. Overall, the results of the calibration and validation steps enriched the proposed model by providing an effective biological description of the processes characterizing the MBR. Thus, the model is a reliable tool for the management and designing of MBR. GRAPHICAL ABSTRACT: